Evaluation of Base Shear Reduction in Reinforced Concrete Buildings Using Fluid Viscous Dampers (FVD) under Time History Earthquake Loads - Windra Pranoto Simatupang; Data Iranata (Universitas Islam Raden Rahmat, Malang, 2026)
This study addresses the seismic vulnerability of a critical hospital in Lamongan, Indonesia, built using outdated codes. The novelty lies in using Nonlinear Time History Analysis (NLTHA) to evaluate site-specific retrofitting for healthcare facilities. By integrating Fluid Viscous Dampers (FVD’s), the research assesses inelastic structural responses under Imperial Valley, Loma Prieta, and Northridge records. Results show that FVD’s reduce base shear by 39.83% in the X-direction and 66.8% in the Y-direction. Despite higher mode effects at mid-levels, the system successfully curbs the top floor whipping effect by 29.12%, safeguarding sensitive medical equipment. For future research, it is recommended to implement nonlinear FVD modeling and life cycle cost analysis to further optimize seismic protection. These findings demonstrate that FVD retrofitting is essential for ensuring post-earthquake hospital functionality, providing a robust framework for upgrading high risk infrastructure in seismic prone regions.